The rheumatodermatology interface - Smitha Prabhu; Mukhyaprana M Prabhu (Wolters Kluwer Medknow Publications, 2019)
Rheumatodermatology is an area of clinical medicine, wherein rheumatological and dermatological features dominate in various connective tissue disorders. It can occur as a systemic rheumatic disease where there is major skin manifestation, inflammatory arthropathies, or complications of immunological dysfunction caused by the rheumatological condition or of the immunosuppressants administered. There are also subtle skin signs of rheumatodermatological conditions which are apparent only to dermatologists and significant joint and internal involvement which may be diagnosed only by the rheumatologist. Hence, a liaison between these two specialties is advisable for optimal management of such diseases.